Designing Coffee Bean Storage Shelves and Rearranging the Layout of the Storage Warehouse in the Coffee Processing Unit of the Solok Sirukam Sepakat Producer Cooperative, Solok Regency - Addin Akbar; Rizaldi Sardani; Suci Oktri Viarani; Wahyu Fitrianda; Dedy Rahmad; Demi Ramadian (LPPM UMRI, 2024)
One of the coffee producers in West Sumatra is the Solok Sirukam Sepakat Producers Cooperative, which has a business line called Agroforestry Unit focusing on coffee cultivation and processing. The brand name of the produced coffee is Solok Sirukam. The main issue currently faced by the cooperative is the storage of coffee beans after drying. So far, the beans have been stored in a disorganized manner on display racks. Additionally, the layout of the storage warehouse does not meet the applicable standards. Therefore, this activity aims to design a proper and adequate coffee bean storage rack to ensure the green beans meet storage standards. This will enable the coffee producers' cooperative to implement good coffee storage practices and produce beans according to proper processing standards. The result of using the newly designed storage rack shows a more organized arrangement. The rack includes tiered shelves with circular metal dividers, which allow for air circulation between the stacks of coffee beans, helping to maintain their moisture. The storage rack is designed to be tiered and columned, allowing for the storage of more coffee beans and grouping products with the same production code, facilitating easier retrieval for the next processing stage.